Experimental Challenge Models and In Vitro Models to Investigate Efficacy of Treatments and Vaccines against Amoebic Gill Disease - Jemma Hudson; Barbara F. Nowak (Microorganisms, 2021)
Amoebic Gill Disease (AGD) severely affects salmonid mariculture due to fish losses and costs associated with management of the disease. Continued research into management solutions, including new treatments and vaccine development, is highly important for the future of salmonid production worldwide. This requires both in vitro (both pathogen only and host-pathogen models) and in vivo (disease challenge) testing. Challenge models are still widely varied, in particular with regard to: infection methods (cohabitation or immersion), source of the pathogen (isolated from infected fish or cultured), infectious dose, environmental conditions (in particular temperature) and the endpoints across experimental treatment and vaccine studies which makes comparisons between studies difficult. This review summarises in vitro assays, the challenge methods and endpoints used in studies of experimental treatments and vaccines for AGD.